The “Cool Men”: power and participation of men in anti-patriarchal activism - Rodríguez Bayona, Jaikel Homero (Centro de Publicaciones Pontificia Universidad Católica del Ecuador, 2019)
In this article we propose reflections regarding the participation of men in anti-patriarchal activism, based on the experience of the Peruvian Network of Masculinities (RPM asc) and the Participatory Action Research (IAP ) process which took place between 2016 and 2017. The participation of men in anti-patriarchal activism is an issue that can be problematic or tense, since men engage from a position of social power which may result in their accumulating prestige through the image of “equalitarian” or “cool” men”. This dilemna can also result in tension and mistrust with other men, especially “machistas” who might consider the former to be “not very manly” because their differing position from the “traditional” one. In this scenario, the need arises to problematize the topic and think about the practices and parameters for men’s anti-patriarchal activism; and the need to support practices that don’t reproduce relationships of domination, but instead contribute to an emancipatory and transformative social movement.